Dal greco classico al greco moderno Alcuni aspetti dell'evoluzione morfosintattica - ZINZI, MARIAROSARIA (Premio Ricerca «Città di Firenze», 2013)
The Greek koinè shows a double development in the crystallised Greek language (intended for literary, administrative and ecclesiastical uses) and the language of everyday use subject to innovations that would lead to the birth neo-Greek, which was never the official language for written documents. This situation determined the almost absolute lack of documents that allow us to reconstruct the evolution of the Greek language from the late age to the early Middle Ages. This work contributes to the reconstruction of this gap by analysing the Greek language of the the private letters written on papyrus, a documentary typology probably close to the spoken register. The analysis isolated four peculiar phenomena of the morphosyntactic evolution of the Greek (genitive-dative syncretism, disappearance of the infinitive, replacement of the perfect tense with equivalent periphrases and disposition of the clitics), offering a renewed picture.